Solution structural model of the complex of the binding regions of human plasminogen with its M-protein receptor from Streptococcus pyogenes - Yuan, Yue (J Struct Biol, 2019)
VEK50 is a truncated peptide from a Streptococcal pyogenes surface human plasminogen (hPg) binding M-protein (PAM). VEK50 contains the full A-domain of PAM, which is responsible for its low nanomolar binding to hPg. The interaction of VEK50 with kringle 2, the PAM-binding domain in hPg (K2(hPg)), has been studied by high-resolution NMR spectroscopy. The data show that each VEK50 monomer in solution contains two tight binding sites for K2(hPg), one each in the a1- (RH1; R(17)H(18)) and a2- (RH2; R(30)H(31)) repeats within the A-domain of VEK50. Two mutant forms of VEK50, viz., VEK50[RH1/AA] (VEK50(△RH1)) and VEK50[RH2/AA] (VEK50(△RH2)), were designed by replacing each RH with AA, thus eliminating one of the K2(hPg) binding sites within VEK50, and allowing separate study of each binding site. Using (13)C- and (15)N-labeled peptides, NMR-derived solution structures of VEK50 in its complex with K2(hPg) were solved. We conclude that the A-domain of PAM can accommodate two molecules of K2(hPg) docked within a short distance of each other, and the strength of the binding is slightly different for each site. The solution structure of the VEK50/K2(hPg), complex, which is a reductionist model of the PAM/hPg complex, provides insights for the binding mechanism of PAM to a host protein, a process that is critical to S. pyogenes virulence.